2011
DOI: 10.1016/j.molonc.2011.02.001
|View full text |Cite
|
Sign up to set email alerts
|

The biology of cancer testis antigens: Putative function, regulation and therapeutic potential

Abstract: Keywords:Cancer testis antigens Published by Elsevier B.V. All rights reserved. IntroductionThe search for tumor-associated antigens (TAA) capable to induce a tumor-directed immune response and the development of cancer vaccines targeting these TAA have been a major effort for the tumor immunology community in the past decades.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
293
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 305 publications
(305 citation statements)
references
References 175 publications
(189 reference statements)
7
293
1
4
Order By: Relevance
“…Many genes that are silent in healthy somatic tissue are specifically activated during the spermatogenic program, providing functions that modulate cellular morphologic changes and meiosis. These genes are known as cancer/testis (CT) genes (or cancer germline genes) when they become aberrantly activated in cancerous tissue (11)(12)(13). The proteins encoded by these genes have garnered interest in the field of clinical oncology as they can potentially serve as targets for immune therapies and expression of CT genes can be applied to patient stratification (for examples, see refs.…”
Section: Activation Of Meiotic Functions In Cancer Cellsmentioning
confidence: 99%
“…Many genes that are silent in healthy somatic tissue are specifically activated during the spermatogenic program, providing functions that modulate cellular morphologic changes and meiosis. These genes are known as cancer/testis (CT) genes (or cancer germline genes) when they become aberrantly activated in cancerous tissue (11)(12)(13). The proteins encoded by these genes have garnered interest in the field of clinical oncology as they can potentially serve as targets for immune therapies and expression of CT genes can be applied to patient stratification (for examples, see refs.…”
Section: Activation Of Meiotic Functions In Cancer Cellsmentioning
confidence: 99%
“…Another important factor for the successful immunotherapy response is the expression of tumor-associated antigens [100]. Along this line, it has been shown that the expression of high molecular weight-melanoma associated antigen (HMW-MAA) is regulated by DNA methylation as its expression correlates with promoter methylation.…”
Section: Epigenetic Alterations and Immunotherapymentioning
confidence: 99%
“…[18][19][20] Of note, TAAs can be (1) viral, in the case of virus-induced tumors (e.g., the E6 and E7 proteins of human papillomavirus type 16, HPV-16, which is associated with cervical and oropharyngeal carcinoma); (2) unique, when they reflect a genetic alteration that is proper of a single cancer cell and its progeny (e.g., the B-cell receptor expressed by some form of lymphoma); (3) tumor-specific, when they are not expressed by normal cells but are found in different neoplasms of the same type (e.g., the BCR-ABL fusion protein, which is expressed by a vast majority of chronic lymphocytic leukemia); (4) shared, when they are expressed by malignant cells as well as by non-transformed cells of some type. [18][19][20]34 Shared TAAs include oncofetal antigens, which are expressed only during embryonic development, as well as cancer-testis antigens, whose normal expression is restricted to male germ cells in the testis 20,[35][36][37][38] Several immunotherapeutic interventions have been developed throughout the past decade to harness TAAs for eliciting tumor-specific adaptive immune responses of therapeutic value. [39][40][41] One of such approaches relies on the administration of purified or recombinant TAAs (or peptides thereof) in the presence of adequate immunostimulatory molecules (so-called adjuvants).…”
Section: Introductionmentioning
confidence: 99%